Is inequality underestimated in Mozambique? Accounting for underreported consumption - Channing Arndt; Kristi Mahrt (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Household budget surveys in sub-Saharan Africa are designed to facilitate poverty measurement and may fail to fully capture consumption in wealthy households. As a result, inequality is likely underestimated. We address upper tier consumption underreporting by aligning consumption derived from Mozambican household surveys with national accounts. Consumption in categories most consumed by wealthy households is more frequently underreported, and therefore scaling household level consumption by category upwardly adjusts upper tier consumption. Using scaled consumption, we find evidence that inequality in Mozambique is underestimated and that inequality began increasing in 2002 rather than 2008 as the official numbers suggest.6000 un
Keywords: D31; D63; E01; O55; 330; consumption underreporting; household surveys; inequality; Mozambique; national accounts